PERAN BRAND AWARENESS MEMEDIASI PENGARUH SOCIAL MEDIA MARKETING TERHADAP PURCHASE INTENTION PRODUK TWISSTERDOG DI DENPASAR - Arashidani, Ananda Matalia; Ekawati, Ni Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2024)
Fast food restaurants are becoming increasingly popular in Indonesia as time goes on. Marketing through social media has become an important strategy for businesses due to technological advancements. This study aims to examine the role of brand awareness as a mediator between social media marketing and purchase intention for Twissterdog products in Denpasar. The research sample consists of 130 respondents who have never purchased Twissterdog products, selected through purposive sampling. Data was collected through questionnaires and analyzed using path analysis, Sobel test, and VAF test. The findings of the research suggest that both social media marketing and brand awareness significantly and positively influence purchase intention. Social media marketing also has a positive and significant influence on brand awareness. Brand awareness is found to mediate the relationship between social media marketing and purchase intention for Twissterdog products in Denpasar. This research has implications for Twissterdog management to update information on social media and enhance the strength of the Twissterdog brand.